The Development of a Woodball Swing Tool Model for UNNES Woodball Students (Student Activity Units) - Sumariyanto, Ahris; Rahayu, Tandiyo; Sulaiman, Sulaiman (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The objective of this study is to produce special tool product for woodball swing basic techniques for Student Activity Units members of the Universitas Negeri Semarang and produce effective tools for the use in the formation process of good and correct basic techniques. This research method used research and development methods. The research results in the form of swing tool product for the woodball swing basic techniques, it is a wood swing, and this tool model is made to facilitate the formation of basic swing techniques. The effectiveness of the tool that is validated by woodball tool experts is 96.4% and woodball trainers 96%, it is in a good category. 41 students use the wood swing tool, 90% in the good category. The conclusion of this study is: it has produced effective swing wood swing tools for the formation of basic techniques for woodball swing. A significant finding that underlies the formation of the wood swing tool is the development of a swing plane model in which the wood swing tool model is devoted to woodball sports. It is suggested that the wood swing tool can help the achievements of woodball athletes at the world level.